2022
DOI: 10.3390/ijms232314541
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Melatonin on Periodontitis Management: Far More Than Oral Cavity

Abstract: Periodontitis as a highly prevalent chronic infection/inflammatory disease can eventually lead to tooth loss and masticatory dysfunction. It also has a negative impact on general health and largely impairs quality of life. The tissue destruction during periodontitis is mainly caused by the excessive immune–inflammatory response; hence, how to modulate the host’s reaction is of profound importance for effective periodontal treatment and tissue protection. Melatonin, as an endogenous hormone exhibiting multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 178 publications
0
5
0
Order By: Relevance
“…This study supports the results of our study which shows an increase in the antimicrobial activity with increasing concentration of melatonin-loaded CaONP-based neem clove extract. According to Wang et al, melatonin reduces the expression of pro-inflammatory cytokines and boosts the levels of antioxidants, thereby reducing the oxidative stress associated with periodontal inflammation [ 21 ]. Similarly while exploring the properties of neem in periodontitis, Elavarasu et al concluded that neem possesses antimicrobial properties using the Mueller-Hinton agar plates method with ZOI ranging from 29-34 mm under various concentrations against oral pathogens [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study supports the results of our study which shows an increase in the antimicrobial activity with increasing concentration of melatonin-loaded CaONP-based neem clove extract. According to Wang et al, melatonin reduces the expression of pro-inflammatory cytokines and boosts the levels of antioxidants, thereby reducing the oxidative stress associated with periodontal inflammation [ 21 ]. Similarly while exploring the properties of neem in periodontitis, Elavarasu et al concluded that neem possesses antimicrobial properties using the Mueller-Hinton agar plates method with ZOI ranging from 29-34 mm under various concentrations against oral pathogens [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gingivitis develops into periodontitis as the inflammation progresses deeper into the deep tissues, leading to loss of attachment and dental bone resorption ( 30 ). In the aforementioned process, cytokine release has the potential to directly destroy periodontal tissues in an irreversible manner as well as indirectly destroy them by altering intracellular signaling and gene expression ( 31 ). Aside from killing harmful bacteria, the respiratory burst of neutrophils can result in excessive production of reactive oxygen species (ROS) and matrix metalloproteinases, which can cause an oxidative imbalance in periodontal tissues and permanent tissue deterioration ( 32 ).…”
Section: Pathogenic Mechanism Of Periodontitismentioning
confidence: 99%
“…These effects of melatonin are closely related to the treatment of periodontitis disease. Indeed, a combination of recent basic studies and clinical studies suggest that melatonin may have potential therapeutic effects on periodontitis [ [28] , [29] , [30] , [31] , [32] ]. In animal studies, melatonin significantly reduced the infiltration of neutrophils in the mandible of rats with experimental periodontitis, eliminated oxygen free radicals, and reduced the secretion of pro-inflammatory cytokines to reduce the destruction of periodontal tissues [ [33] , [34] , [35] , [36] ].…”
Section: Introductionmentioning
confidence: 99%